Extraction of antioxidant phenolic compounds from spent coffee grounds - Mussatto, Solange I. (2011)
The extraction of antioxidant phenolic compounds from spent coffee grounds (SCG) was studied. Extraction experiments were carried out by the conventional solid–liquid method, using methanol as solvent at different concentrations (20–100%), solvent/solid ratios (10–40 ml/g SCG), and extraction times (30–90 min), and the influence of these operational variables on the content of total phenolic compounds and antioxidant activity of the produced extracts was evaluated. Flavonoids, chlorogenic acid, and protocatechuic acid were found in all the produced extracts and were also quantified. A strong influence (p < 0.05) of the variables on the extraction results was verified, and the conditions able to maximize each response (contents of total phenolic compounds, flavonoids, chlorogenic acid and protocatechuic acid, and antioxidant activity) were established. Extraction using 60% methanol in a solvent/solid ratio of 40 ml/g SCG, during 90 min, was the most suitable condition to produce a extract with high content of phenolic compounds (16 mg gallic acid equivalents/g SCG) and high antioxidant activity (FRAP of 0.10 mM Fe(II)/g), simultaneously. These findings are of interest since antioxidant phenolic compounds have an outstanding role in health area, and wide applications in food and pharmaceutical products.